2020
DOI: 10.1007/s10509-019-3717-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the region of the rings and small satellites of Neptune

Abstract: The ring system and small satellites of Neptune were discovered during Voyager 2 flyby in 1989 (Smith et al. 1989). In this work we analyse the diffusion maps which can give an overview of the system. As a result we found the width of unstable and stable regions close to each satellite. The innermost Galle ring, which is further from the satellites, is located in a stable region, while Lassel ring (W = 4000 km) has its inner border in a stable region depending on its eccentricity. The same happens to the Le Ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The former were assumed by us as the building blocks of the moonlets, while the latter may have contributed to the formation of the arcs. As shown in Gallardo et al ( 2020 ), the dust material in the Adams ring region has a short lifetime due to solar radiation and plasma drag, so macroscopic debris are the most likely to have contributed to the formation of the arcs.…”
Section: Moon Disruption Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The former were assumed by us as the building blocks of the moonlets, while the latter may have contributed to the formation of the arcs. As shown in Gallardo et al ( 2020 ), the dust material in the Adams ring region has a short lifetime due to solar radiation and plasma drag, so macroscopic debris are the most likely to have contributed to the formation of the arcs.…”
Section: Moon Disruption Stagementioning
confidence: 99%
“…We emphasize that the type of impactor influences the sizes of the launched particles. The impacts of IDPs produce micrometre particles (1-100 μm) that suffer the effects of dissipative forces, such as the solar radiation force and plasma drag (see Gallardo et al 2020 ). Giuliatti showed that the lifetime of micrometre particles in the arcs under the effects of the solar radiation force is less than 50 yr and that moonlets cannot replenish the arcs by IDP impacts.…”
Section: Post-formation Stagementioning
confidence: 99%